Friday

April 18, 2014

April 18, 2014

Posted by **liv** on Thursday, October 19, 2006 at 9:41pm.

-3n squared +4m

4m+(-3n)+n = 4m + n(-3 +1) = 4m +(-2n) = 2(2m -n)

**Related Questions**

Math - How would you find the value of m in this problem? 4m + 2 = -2 + 4m Well...

math b - i want to know if this is correct expand the following without using ...

Algebra - Simplify: (4m/5n^2)-(n/2m) A)(8m^2-5n^3)/10n^2m B)(8m^2+5n^3)/10n^2m C...

math - If m+3n =20 and p =7, then 4m+12n +3p=

algebra - How would you solve this? I don't even know how to begin this... I ...

algebra - - #21 -can you help me solve this equation: 3x^2 (2x - 2) i keep ...

pre algebra - what is 3y+2(-7+x) First, we need to distribute. 2 times -7 is -14...

Math - 10=1x - 3 4m-4 =4m

physics - Two identical negative charges are located on the y axis, at y = +4m ...

Math[more] - Directions:Subtract and simplify. Problem: m+9/(m+3)-(-4m-6)/(m+3) ...